Chemical footprints mediate habitat selection in co-occurring aphids. (20th August 2022) - Porras, Mitzy F; McCartney, Nathaniel; Raspotnig, Günther; Rajotte, Edwin G
Abstract: Habitat selection is a critical process that shapes the spatial distribution of species at local and regional scales. The mechanisms underlying habitat preference rely on environmental factors, species traits, and ecological interactions with other species. Here, we examined spatial segregation between two co-occurring aphid species ( Rhopalosiphum maidis and R. padi ) on wheat plants. We hypothesized that spatial segregation between these aphid species was mediated by aphid cuticular compounds left as chemical "footprints" on plant surfaces. Combining field and laboratory experiments, we first examined how plant microsites alter fitness by measuring the fecundity of each species. Next, we tested whether intra- and interspecific pre-inhabitation modified habitat selection in both aphid species. Both aphid species preferred and exhibited higher fecundity on wheat stems versus leaves. Laboratory trials showed that R. maidis pre-inhabitation altered R. padi spatial preference. By gas chromatography-mass spectrometry analysis and bioassays testing the effects of aphid density and footprint extracts, we found a density-dependent response, with R. padi avoiding locations previously inhabited by R. maidis . The chemical analysis of footprint crude extracts revealed a highly abundant compound, 1-hexacosanol, and when presented in the synthetic form, also elicited R. padi displacement. Altogether, it indicated that R. maidis footprints altered R. padi habitat selection with cuticular compounds playing a relevant role in the habitat selection process in co-occurring aphid species. Abstract : Traits like body size, thermal sensitivity, and pheromone production/response can alter a species' habitat preferences with implications for the ways animals compete for limited resources. We used field and laboratory experiments to explore how two aphid species compete for the same host plant microsites. We showed that a cuticular chemical signal deposited by the competitor aphid species contributes to spatial segregation between the co-occurring species.